2019
DOI: 10.1136/vr.105472
|View full text |Cite
|
Sign up to set email alerts
|

Do UK sheep farmers use orf vaccine correctly and could their vaccination strategy affect vaccine efficacy?

Abstract: Orf, a parapoxvirus, is a zoonosis causing a contagious pustular dermatitis, and has a high morbidity in sheep worldwide. Despite a vaccine being available, orf prevalence in England is estimated to be 2 per cent in ewes and 20 per cent in lambs​​. There is concern that farmers are not complying with the vaccination guidelines and therefore the objective of this study was to investigate if orf vaccine is used correctly on sheep farms in the UK and to identify barriers and motivators of sheep farmers to use the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 19 publications
2
16
0
1
Order By: Relevance
“…However, the ability of the virus to repeatedly infect the susceptible host does not appear to be associated with the production of the desired memory T-cells as a promising hypersensitivity reaction to ORFV antigen, as reported by several recent publications [54,79,83,129]. Thus, such an immune response cannot be considered abnormal for ORFV infection, as significant levels of CD4 + T-cells have been detected among the infected animals when compared to CD8 + cytotoxic T-cells and/or B-cell response [115,[130][131][132][133][134][135]. On the other hand, the humoral immune response does not play an important role in protecting animals from ORFV infection [136].…”
Section: Innate and Adaptive Immune Responses Against Orfv Infectionmentioning
confidence: 85%
See 3 more Smart Citations
“…However, the ability of the virus to repeatedly infect the susceptible host does not appear to be associated with the production of the desired memory T-cells as a promising hypersensitivity reaction to ORFV antigen, as reported by several recent publications [54,79,83,129]. Thus, such an immune response cannot be considered abnormal for ORFV infection, as significant levels of CD4 + T-cells have been detected among the infected animals when compared to CD8 + cytotoxic T-cells and/or B-cell response [115,[130][131][132][133][134][135]. On the other hand, the humoral immune response does not play an important role in protecting animals from ORFV infection [136].…”
Section: Innate and Adaptive Immune Responses Against Orfv Infectionmentioning
confidence: 85%
“…More recent studies demonstrated that plasmid DNA-based ORFV vaccines derived from virulent strains induced protective T cells and ORFV-specific antibody responses in neonates [3,27,64,130,135]. The result indicated that the plasmid DNA-based vaccines induced similar responses in mice compared to live-attenuated vaccines [179].…”
Section: Cell Culture-based Vaccinementioning
confidence: 99%
See 2 more Smart Citations
“…Mortality due to ORFV infections is rarely associated with secondary infections and aspiration pneumonia. In general, orf disease is a threat to kids and lambs and may cause farms to suffer economic losses [90][91][92][93][94].…”
Section: Orf Virusmentioning
confidence: 99%